The Social Cost of Carbon: Valuing Inequality, Risk, and Population for Climate Policy. (20th December 2018) - Fleurbaey, Marc; Ferranna, Maddalena; Budolfson, Mark; Dennig, Francis; Mintz-Woo, Kian; Socolow, Robert; Spears, Dean; Zuber, Stéphane
Abstract: We analyze the role of ethical values in the determination of the social cost of carbon, arguing that the familiar debate about discounting is too narrow. Other ethical issues are equally important to computing the social cost of carbon, and we highlight inequality, risk, and population ethics. Although the usual approach, in the economics of cost-benefit analysis for climate policy, is confined to a utilitarian axiology, the methodology of the social cost of carbon is rather flexible and can be expanded to a broader set of social-welfare approaches.